Proccedings of International Scientific Conference "RURAL DEVELOPMENT 2017" 2018
DOI: 10.15544/rd.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mg and S on Photosynthesis Products and Nitrogen Content in Winter Wheat

Abstract: In 2013 and 2014, field experiments involving winter wheat were conducted at Aleksandras Stulginskis University's Experimental Station on a medium-textured Cal(ca)ri-Epihypogleyic Luvisol. N150P90K120 were applied as the main fertilizers. Additionally, a foliar fertilizer including amide nitrogen, sulphur and magnesium (MgO concentrations ranging from 0.25 % to 2.5 %), (further referred to as magnesium fertilizer), was sprayed at the tillering and booting stages of winter wheat. It was found that magnesium fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Similarly, Dromantienė et al. (2017) observed that foliar application of Mg at various stages of wheat development provided the highest increase in DM and yield. Magnesium fertilizer application can not only improve the chlorophyll concentration and reduce protein depletion, but it can also enhance the total plant biomass and increase crop yields (Hauer‐Jákli & Tränkner, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, Dromantienė et al. (2017) observed that foliar application of Mg at various stages of wheat development provided the highest increase in DM and yield. Magnesium fertilizer application can not only improve the chlorophyll concentration and reduce protein depletion, but it can also enhance the total plant biomass and increase crop yields (Hauer‐Jákli & Tränkner, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Many studies have proven that optimal application of Mg fertilizer can improve the chlorophyll, N, K, Mg, and other nutrient contents of the crop, thus improving the biomass and economic yield (Ferdous, Anwar, Haque, Mahamud, & Hossain, 2014;Laxminarayana & Susan John, 2014). Similarly, Dromantienė et al (2017) observed that foliar application of Mg at various stages of wheat development provided the highest increase in DM and yield. Magnesium fertilizer application can not only improve the chlorophyll concentration and reduce protein depletion, but it can also enhance the total plant biomass and increase crop yields (Hauer-Jákli & Tränkner, 2019).…”
Section: Maize Total Dry Matter and Grain Yieldmentioning
confidence: 78%
“…Numerous studies have been addressed that Mg fertilizers significantly increase the straw yield of the shoots, and the total DM of a maize crop influences the grain yield . Similarly, Dromantien et al . observed that foliar application of Mg at various stages of wheat growth provided highest increase in DM and yield.…”
Section: Discussionmentioning
confidence: 99%